Voice in Motion : Staging Gender, Shaping Sound in Early Modern England - Bloom, Gina (Book collections on Project MUSE., 2007)
"Voice in Motion explores the human voice as a literary, historical, and performative motif in early modern English drama and culture, where the voice was frequently represented as struggling, even failing, to work. In an original argument, Gina Bloom demonstrates that early modern ideas about the efficacy of spoken communication spring from an understanding of the voice's materiality." "Bringing together performance theory, theater history, theories of embodiment, and sound studies, this book makes a significant contribution to gender studies and feminist theory by challenging traditional conceptions of the links among voice, body, and self."--Jacket.